Doped catalyst based on carbon nanotube
By forming an organic metal frame and a nitrogen-doped carbon frame on the surface of carbon nanotubes, the problems of low conversion rate and catalyst cycle times in the existing low-carbon alcohol synthesis process are solved, and efficient low-carbon alcohol synthesis and long life of the catalyst are achieved.
Patent Information
- Application Number
- CN202411824410.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The conversion rate and catalyst cycle times of the existing low-carbon alcohol synthesis process limit its application value.
Using a doped catalyst based on carbon nanotubes, an organic metal frame is formed by introducing carboxy group anchor Co2+ on the surface of the carbon nanotube, and a surface nitrogen-doped carbon skeleton is prepared by calcining to enhance the activity and cycle times of the catalyst.
The conversion rate of low-carbon alcohol synthesis is significantly improved, and the number of cycles of the catalyst is improved, which improves the stability and application efficiency of the catalyst.
Smart Images

Figure CN119565654A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically refers to a doped catalyst based on carbon nanotubes. Background Art
[0002] Low-carbon alcohol is an ideal high-octane, low-pollution automotive fuel additive. It can be mixed with gasoline to form alcohol-oil hybrid fuel, and can also be used as an ideal cosolvent for methanol-gasoline hybrid fuel. In recent years, oil has become increasingly scarce, and the amount of gasoline mixed with methanol as a hybrid fuel has increased. The practical value of low-carbon alcohol as an oil additive or oil-alcohol cosolvent has continued to increase. The existing low-carbon alcohol synthesis process has a low single-pass conversion rate and selectivity for generating alcohol, which greatly limits its application. Carbon nanotubes are similar in structure to hollow graphite fibers, but have a higher structural regularity, with graphitized tube walls, nanometer-scale tube cavities, and sp 2 -C surface, and exhibits good electrical and thermal conductivity, as well as excellent performance in activating the adsorption of H2 and promoting the overflow of adsorbed hydrogen, which makes it very promising to become an efficient promoter of some hydrogenation catalysts.
[0003] The existing technologies currently have the following main problems: low conversion rate of low-carbon alcohol synthesis and low number of catalyst cycles. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a doped catalyst based on carbon nanotubes. In order to solve the problems of low synthesis conversion rate of low-carbon alcohols and low catalyst cycle number, the present invention proposes to improve the synthesis conversion rate of low-carbon alcohols by preparing a doped catalyst based on carbon nanotubes. At the same time, Cu-Co is fixed on the surface of carbon nanotubes with an organic framework, and a surface nitrogen-doped carbon skeleton is prepared by calcination, thereby achieving the technical effect of improving the number of catalyst cycles.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a doped catalyst based on carbon nanotubes, and the doped catalyst based on carbon nanotubes includes the following components in parts by weight: 150-200 parts of carbon nanotubes, 12-15 parts of cobalt nitrate hexahydrate, 10-12 parts of dimethylimidazole, and 12-16 parts of copper nitrate trihydrate.
[0006] The present invention also provides a method for preparing a doped catalyst based on carbon nanotubes, which specifically comprises the following steps:
[0007] S1, adding carbon nanotubes to concentrated nitric acid, stirring in an oil bath, filtering, washing, and drying to obtain carboxylated carbon nanotubes;
[0008] S2, adding cobalt nitrate hexahydrate to deionized water, stirring and dissolving to obtain a cobalt nitrate solution, and adding copper nitrate trihydrate to deionized water, stirring and dissolving to obtain a copper nitrate solution;
[0009] S3, adding the carboxylated carbon nanotubes obtained in S1 to the cobalt nitrate solution obtained in S2, ultrasonically dispersing for 15 minutes, then adding dimethylimidazole, stirring in an oil bath, filtering, washing, and drying to obtain ZIF-67 / CNT;
[0010] S4, adding the ZIF-67 / CNT obtained in S3 to the copper nitrate solution obtained in S2, ultrasonically dispersing for 30 minutes, immersing for 2-3 hours, filtering, and obtaining Cu / ZIF / CNT;
[0011] S5. Transfer the Cu / ZIF / CNT obtained in S4 to a tubular furnace, heat and calcine for 2-3 hours in a nitrogen atmosphere, then raise the temperature to 500-600°C and continue calcining for 3-5 hours in a hydrogen atmosphere to obtain Cu-Co / N-CNT, and cool to room temperature to obtain a doped catalyst based on carbon nanotubes.
[0012] Preferably, in S1, the amount of the carbon nanotubes added to the concentrated nitric acid is 0.03-0.05 g / mL.
[0013] Preferably, in S2, the amount of cobalt nitrate hexahydrate added to deionized water is 0.04-0.05 g / mL.
[0014] Preferably, in S2, the amount of copper nitrate trihydrate added to deionized water is 0.08-0.1 g / mL.
[0015] Preferably, in S3, the oil bath is stirred at a temperature of 80-90°C, a speed of 50-60 rpm, and a time of 5-6 h.
[0016] Preferably, in S5, the heating temperature is increased at a rate of 3.8-4.6°C / min, and the final temperature is 320-350°C.
[0017] The beneficial effects achieved by the present invention are as follows: by modifying the carbon nanotubes, carboxyl groups are introduced on the surface of the carbon nanotubes to anchor Co 2+ As nucleation sites, Co 2+ As the central ion, it forms a coordination bond with dimethylimidazole and acts as a ligand to induce the formation of an organic metal framework fixed on the surface of carbon nanotubes to form a necklace-like structure. 2+ After calcination, an N-doped C skeleton is formed to form a new active center, thereby improving the synthesis conversion rate of low-carbon alcohols. At the same time, Co-Cu is fixed on the surface of carbon nanotubes with an organic framework, and a surface nitrogen-doped carbon skeleton is prepared by calcination to increase the number of catalyst cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The results of the CO conversion rate test of the synthesis gas of Example 1-3 and Comparative Example 1-2 are shown in FIG.
[0019] Figure 2 Synthesis gas test C for Examples 1-3 and Comparative Examples 1-2 1-8 Results graph of alcohol selectivity;
[0020] Figure 3 The conversion results of Example 1-3 and Comparative Example 1-2 when the experiment was performed 50 times;
[0021] Figure 4 The SEM images of the experiment of Example 1 were performed 50 times;
[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0025] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.
[0026] Example 1
[0027] A doped catalyst based on carbon nanotubes comprises the following components in parts by weight: 150 parts of carbon nanotubes, 12 parts of cobalt nitrate hexahydrate, 10 parts of dimethylimidazole, and 12 parts of copper nitrate trihydrate.
[0028] The preparation method of the doped catalyst based on carbon nanotubes specifically comprises the following steps:
[0029] S1, adding carbon nanotubes in an amount of 0.03 g / mL into concentrated nitric acid, stirring in an oil bath, filtering, washing, and drying to obtain carboxylated carbon nanotubes;
[0030] S2, adding cobalt nitrate hexahydrate in an amount of 0.04 g / mL to deionized water, stirring to dissolve, to obtain a cobalt nitrate solution, adding copper nitrate trihydrate in an amount of 0.08 g / mL to deionized water, stirring to dissolve, to obtain a copper nitrate solution;
[0031] S3, adding the carboxylated carbon nanotubes obtained in S1 to the cobalt nitrate solution obtained in S2, ultrasonically dispersing for 15 min, then adding dimethyl imidazole, stirring at 80-90°C oil bath at 50-60 rpm for 5-6 h, filtering, washing, and drying to obtain ZIF-67 / CNT;
[0032] S4, adding the ZIF-67 / CNT obtained in S3 to the copper nitrate solution obtained in S2, ultrasonically dispersing for 30 minutes, immersing for 2-3 hours, filtering, and obtaining Cu / ZIF / CNT;
[0033] S5. Transfer the Cu / ZIF / CNT obtained in S4 to a tubular furnace, heat to 320°C at 3.8°C / min, calcine for 2 h in a nitrogen atmosphere, then heat to 500°C and continue calcining for 3 h in a hydrogen atmosphere to obtain Cu-Co / N-CNT. Cool to room temperature to obtain a doped catalyst based on carbon nanotubes.
[0034] Example 2
[0035] A doped catalyst based on carbon nanotubes comprises the following components in parts by weight: 200 parts of carbon nanotubes, 15 parts of cobalt nitrate hexahydrate, 12 parts of dimethylimidazole, and 16 parts of copper nitrate trihydrate.
[0036] The preparation method of the doped catalyst based on carbon nanotubes specifically comprises the following steps:
[0037] S1, adding carbon nanotubes in an amount of 0.05 g / mL into concentrated nitric acid, stirring in an oil bath, filtering, washing, and drying to obtain carboxylated carbon nanotubes;
[0038] S2, adding cobalt nitrate hexahydrate in an amount of 0.05 g / mL to deionized water, stirring to dissolve, to obtain a cobalt nitrate solution, adding copper nitrate trihydrate in an amount of 0.1 g / mL to deionized water, stirring to dissolve, to obtain a copper nitrate solution;
[0039] S3, adding the carboxylated carbon nanotubes obtained in S1 to the cobalt nitrate solution obtained in S2, ultrasonically dispersing for 15 min, then adding dimethyl imidazole, stirring at 60 rpm in an oil bath at 90°C for 6 h, filtering, washing, and drying to obtain ZIF-67 / CNT;
[0040] S4, adding the ZIF-67 / CNT obtained in S3 to the copper nitrate solution obtained in S2, ultrasonically dispersing for 30 minutes, immersing for 3 hours, filtering, and obtaining Cu / ZIF / CNT;
[0041] S5. Transfer the Cu / ZIF / CNT obtained in S4 to a tubular furnace, heat to 350°C at 4.6°C / min, calcine for 3 h in a nitrogen atmosphere, then heat to 600°C and continue calcining for 5 h in a hydrogen atmosphere to obtain Cu-Co / N-CNT. Cool to room temperature to obtain a doped catalyst based on carbon nanotubes.
[0042] Example 3
[0043] A doped catalyst based on carbon nanotubes comprises the following components in parts by weight: 170 parts of carbon nanotubes, 13 parts of cobalt nitrate hexahydrate, 11 parts of dimethylimidazole, and 14 parts of copper nitrate trihydrate.
[0044] The preparation method of the doped catalyst based on carbon nanotubes specifically comprises the following steps:
[0045] S1, adding carbon nanotubes in an amount of 0.04 g / mL to concentrated nitric acid, stirring in an oil bath, filtering, washing, and drying to obtain carboxylated carbon nanotubes;
[0046] S2, adding cobalt nitrate hexahydrate in an amount of 0.045 g / mL to deionized water, stirring to dissolve, to obtain a cobalt nitrate solution, adding copper nitrate trihydrate in an amount of 0.09 g / mL to deionized water, stirring to dissolve, to obtain a copper nitrate solution;
[0047] S3, adding the carboxylated carbon nanotubes obtained in S1 to the cobalt nitrate solution obtained in S2, ultrasonically dispersing for 15 min, then adding dimethyl imidazole, stirring at 55 rpm in an oil bath at 85°C for 5-6 h, filtering, washing, and drying to obtain ZIF-67 / CNT;
[0048] S4, adding the ZIF-67 / CNT obtained in S3 to the copper nitrate solution obtained in S2, ultrasonically dispersing for 30 min, immersing for 2.5 h, filtering, and obtaining Cu / ZIF / CNT;
[0049] S5. Transfer the Cu / ZIF / CNT obtained in S4 to a tubular furnace, heat to 335°C at 4°C / min, calcine for 2.5 h in a nitrogen atmosphere, then heat to 550°C and continue calcining for 4 h in a hydrogen atmosphere to obtain Cu-Co / N-CNT. Cool to room temperature to obtain a doped catalyst based on carbon nanotubes.
[0050] Comparative Example 1
[0051] This comparative example provides a catalyst, which is different from Example 1 only in that no organic metal skeleton is prepared in all components, that is, carbon nanotubes are loaded with Co-Cu by impregnation, and the other components and component contents are the same as those in Example 1.
[0052] Comparative Example 2
[0053] This comparative example provides a catalyst, which is different from Example 1 only in that carbon nanotubes are not contained in all components, that is, Co-Cu is loaded only by preparing an organic metal skeleton and a nitrogen-containing carbon skeleton, and the other components and component contents are the same as those in Example 1.
[0054] Experimental example
[0055] 1. Syngas testing
[0056] In the test, the amount of catalyst used in each group of Examples 1-3 and Comparative Examples 1-2 was 0.5 g. Hydrogen was introduced before the reaction for reduction. The hydrogen flow rate was 60 mL / min, the temperature was 400 ° C, and the time was 8 h. The synthesis gas with a raw material composition of V (H2) / V (CO) / V (CO2) / V (N2) = 45 / 45 / 5 / 5 was introduced for reaction. The reaction temperature was adjusted to 300 ° C, the pressure was 5.0 MPa, and the gas hourly space velocity was 8000 mL / h / g for synthesis. The CO conversion rate was calculated by the N2 internal standard method, and C 1-8 Alcohol selectivity was calculated by the C-group normalization method;
[0057] Figure 1 The figure is a result graph of the CO conversion rate of the synthesis gas test of Examples 1-3 and Comparative Examples 1-2; as shown in the figure, when the experiment is carried out once, the conversion rates of Examples 1-3 and Comparative Examples 1-2 are 53.2%, 52.6%, 51.5%, 33.9% and 36.7%, respectively; when the experiment is carried out once, the conversion rate of Example 1-3 is significantly higher than that of Comparative Examples 1-2, and the catalyst prepared by calcining the organic metal framework has a larger specific surface area and pore volume, and is firmly wrapped on the surface of the carbon nanotubes, which is conducive to the absorption of the synthesis gas and the progress of the reaction.
[0058] Figure 2 Synthesis gas test C for Examples 1-3 and Comparative Examples 1-2 1-8 Result diagram of alcohol selectivity; as shown in the figure, when the experiment was performed once, the selectivities of Example 1-3 and Comparative Example 1-2 were 78.2%, 76.1%, 77.1%, 59.6%, and 60.1%, respectively.
[0059] 2. Stability test
[0060] The above conversion rate test was repeated 50 times and the conversion rate was recorded.
[0061] Figure 3The result diagram of the conversion rate when the experiment of Examples 1-3 and Comparative Examples 1-2 was performed 50 times; as shown in the figure, when the experiment was performed 50 times, the conversion rates of Examples 1-3 and Comparative Examples 1-2 were 50.1%, 49.6%, 50.7%, 10.3%, and 20.1%, respectively; when the experiment was performed 50 times, the conversion rate of Examples 1-3 was significantly higher than that of Comparative Example 1, and the Figure 1 The decrease in data conversion rate is significantly lower than that in Comparative Example 1, indicating that Examples 1-3 can be reused.
[0062] Figure 4 This is an SEM image of Example 1 after 50 experiments. As shown in the figure, after 50 catalytic experiments, the dispersion of the product is still good, and there is no obvious aggregation phenomenon, which shows that the catalyst has good stability.
[0063] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0064] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A doped catalyst based on carbon nanotubes, characterized in that: The invention comprises the following components in parts by weight: 150-200 parts of carbon nanotubes, 12-15 parts of cobalt nitrate hexahydrate, 10-12 parts of dimethylimidazole, and 12-16 parts of copper nitrate trihydrate; The preparation method of the doped catalyst based on carbon nanotubes specifically comprises the following steps: S1, adding carbon nanotubes to concentrated nitric acid, stirring in an oil bath, filtering, washing, and drying to obtain carboxylated carbon nanotubes; S2, adding cobalt nitrate hexahydrate to deionized water, stirring and dissolving to obtain a cobalt nitrate solution, and adding copper nitrate trihydrate to deionized water, stirring and dissolving to obtain a copper nitrate solution; S3, adding the carboxylated carbon nanotubes obtained in S1 to the cobalt nitrate solution obtained in S2, ultrasonically dispersing for 15 minutes, then adding dimethylimidazole, stirring in an oil bath, filtering, washing, and drying to obtain ZIF-67 / CNT; S4, adding the ZIF-67 / CNT obtained in S3 to the copper nitrate solution obtained in S2, ultrasonically dispersing for 30 minutes, immersing for 2-3 hours, filtering, and obtaining Cu / ZIF / CNT; S5. Transfer the Cu / ZIF / CNT obtained in S4 to a tubular furnace, heat and calcine for 2-3 hours in a nitrogen atmosphere, then raise the temperature to 500-600°C and continue calcining for 3-5 hours in a hydrogen atmosphere to obtain Cu-Co / N-CNT, and cool to room temperature to obtain a doped catalyst based on carbon nanotubes.
2. The carbon nanotube-based doped catalyst according to claim 1, characterized in that: In S1, the amount of the carbon nanotubes added to the concentrated nitric acid is 0.03-0.05 g / mL.
3. The carbon nanotube-based doped catalyst according to claim 2, characterized in that: In S2, the amount of cobalt nitrate hexahydrate added to deionized water is 0.04-0.05 g / mL.
4. The carbon nanotube-based doped catalyst according to claim 3, characterized in that: In S2, the copper nitrate trihydrate is added in an amount of 0.08-0.1 g / mL in deionized water.
5. The carbon nanotube-based doped catalyst according to claim 4, characterized in that: In S3, the oil bath is stirred at a temperature of 80-90°C, a speed of 50-60 rpm, and a time of 5-6 hours.
6. The carbon nanotube-based doped catalyst according to claim 5, characterized in that: In S5, the heating temperature is increased at a rate of 3.8-4.6°C / min, and the final temperature is 320-350°C.
Citation Information
Patent Citations
Carbon nano tube composite nanometer cobalt-copper alloy catalyst for low-carbon alcohol synthesis and preparation method of carbon nano tube composite nanometer cobalt-copper alloy catalyst
CN104475106A
Promoting cobalt-copper base catalyst for preparation of low carbon mixed alcohol-carbon nano tube from synthetic gas and preparing method thereof
CN1669649A
Method of synthesizing carbon nanofiber using cobalt-copper based catalyst and carbon nanofiber synthesized thereby
KR101452728B1
synthetic method of Si-CNFs based on Co-Cu catalysts
KR1020150133333A
Preparation method for and use of solvent coordination metal catalyst
WO2022166084A1